ANALISA ALIRAN DAYA SISTEM 20kV PADA PROYEK TUJUH BUKIT POWER SYSTEM MENGGUNAKAN SOFTWARE ETAP 12.6 - Iriandi Ilyas; Bagas Arief Apri; Edy Supriyadi; Abdul Multi (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT Power flow analysis is important in planning in order to get a good electric power system. In planning the electrical system for the Tujuh Bukit Power System project with a 20kV system network located in Banyuwangi, East Java, a power flow simulation for a single line diagram will be carried out using the ETAP 12.6 software with the Newton Raphson method. The simulation results which consist of 22 buses show a voltage drop on the 0.4kV_ADR MCC Busbar2 bus and 0.4kV_50-MCC-01 Busbar2 bus. As a system improvement, the 0.4kV_ADR MCC Busbar2 bus will be installed with a 500 kVar capacitor bank to raise the voltage profile from 376.3 V to 385.56 V. While on the 0.4kV_50-MCC-01 Busbar2 bus, a 100 kVar capacitor bank is required to increase the voltage from 382.2 V to 384.16 V. After the repair, the power supplied to the system is 3589.6 kVA with a power factor of 90.5% lagging. As well as the reduction in the total value of system power losses from 58.1 kW + 242.2 kVar to 49.3 kW + 200.8 kVar. Keywords: Power flow, Netwon Rapshon, Simulation, Software ETAP 12.6